(untitled) (Research, Society and Development, 2023)
According to Article 6 of the Federal Constitution of 1988, everyone has the right to leisure and health, such practices have been made possible by the Recreation Extension Project for Elderly People (Recrear). The project takes leisure activities and health education actions to the elderly population and their caregivers. This work reports the experience of the actions promoted by the Recrear project at UBS Vila Mariana in São Paulo/SP, in 2022. It is an experience report of the actions of the project at UBS Vila Mariana, in São Paulo, SP. The team consisted of thirteen undergraduate nursing students, one graduate student and seven professors from the Escola Paulista de Enfermagem (EPE) belonging to the Federal University of São Paulo (UNIFESP). Constituting a participatory group of elderly people assisted by the UBS, which allowed the link between extension workers and the target audience. During the meetings, 17 activities were developed, such as: board games, June festival, auriculotherapy, meditation and educational action “Diet and Light”. Thus, the actions performed allowed the maintenance of the functional capacity and the socialization of the elderly; it made it possible to face prejudice against the elderly; improved academic training and contributed to healthy aging. In short, the project has an educational, cultural and scientific nature that articulates, in an inseparable way, teaching, extension, research, assistance and the community, enabling a transforming relationship between institution, university and society.